2006
DOI: 10.1007/s11661-006-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phase transformations on the mechanical properties of high-strength austenitic Fe-Mn-Cr steel

Abstract: The influence of Cr and N additions on the mechanical properties of a Fe-Mn-C steel was investigated. The chemical composition was found to have a pronounced effect on the strain-hardening behavior, due to the strain-induced sequence of the ␥ : : ␣Ј martensitic transformations. It was found that Cr and N suppress this transformation sequence. At Cr levels higher than 7.5 mass pct, no ␣Ј martensite was formed, which led to a pronounced improvement of the ductility. The differences in transformation behavior can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 26 publications
4
48
0
2
Order By: Relevance
“…In a previous article, [44] it was illustrated that the low Cr in the hotrolled and annealed condition does not show a beneficial transformation induced plasticity (TRIP) effect, contrary to what is commonly observed in Fe-Cr-Ni-based austenitic steels, e.g., AISI 301. The latter have a sudden increase of strain hardening at a tensile strain of about 15 pct as a result of the strain-induced c fi a¢ martensitic transformation.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a previous article, [44] it was illustrated that the low Cr in the hotrolled and annealed condition does not show a beneficial transformation induced plasticity (TRIP) effect, contrary to what is commonly observed in Fe-Cr-Ni-based austenitic steels, e.g., AISI 301. The latter have a sudden increase of strain hardening at a tensile strain of about 15 pct as a result of the strain-induced c fi a¢ martensitic transformation.…”
Section: Discussionmentioning
confidence: 89%
“…[35,45] In the low Cr alloy in the hot-rolled and annealed condition, the kinetics is very fast, especially for the c fi e-martensite transformation. [44] This is also reflected in the high strain-hardening value at low strains, n 1-5 . Reducing the amount of e-martensite formed in the early stages of the deformation is expected to result in a better TRIP effect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[13] TWIP steels presented a dimpled and ductile fracture surface under scanning electron microscopy investigation. [14] The evolution of ductile damage was investigated by three-dimensional X-ray tomography in situ tensile test. It was found that the ductile damage process of TWIP steels involved intense nucleation of small voids combined with the significant growth of the biggest cavities.…”
Section: Abstract: High Manganese Steels Deformation Microstructurementioning
confidence: 99%
“…At low Mn content or at high deformation degrees, besides ε-hcp, α' (body centre cubic, bcc) martensite can be additionally induced by cooling or deformation [14].…”
Section: Introductionmentioning
confidence: 99%